Axicabtagene Ciloleucel as Second-Line Therapy for Large B-Cell Lymphoma - Locke, Frederick L; Miklos, David B; Jacobson, Caron A; Perales, Miguel-Angel; Kersten, Marie-José; Oluwole, Olalekan O; Ghobadi, Armin; Rapoport, Aaron P; McGuirk, Joseph; Pagel, John M; Muñoz, Javier; Farooq, Umar; et al. (The New England journal of medicine, 2022)
In a trial involving patients with relapsed or refractory large B-cell lymphoma, the CAR T-cell therapy axicabtagene ciloleucel led to significantly longer event-free survival than standard salvage chemotherapy (which was followed by high-dose therapy and autologous stem-cell transplantation in patients with a response). High-grade toxic effects were common, but most patients recovered.